Evaluasi Kerusakan Jembatan Komposit dan Jembatan Rangka - Hamzah; Athaya Zhafirah (Institut Teknologi Garut, 2023)
Damage to a bridge can affect bridge performance due to the age of the bridge, the load carried, climatic conditions, or traffic intensity. Bridges that are seriously damaged and not properly evaluated can endanger the safety of users who cross them. The aim of this research is to identify and analyze damage to composite and frame type bridges in Garut Regency. Evaluation of bridge damage uses the Bridge Management System (BMS) method, based on the data required in this research including bridge administration data and bridge condition data carried out by direct survey in the field. The results of the inspection and evaluation using the Bridge Management System are known to be in accordance with level 1 points based on the condition of each bridge. The numbers obtained from the analysis of the Cimanuk Bridge on Jalan Printis are 2; Damage monitoring and maintenance will be required in the future. Cimanuk Bridge Jalan Cinunuk bridge condition score 3; Damage should be noted as it could be severe over the next 12 months. Kadungora-Leles Alternative Road Flyover Bridge condition value of the bridge 2 Damage monitoring and maintenance will be required in the future. Maleer/Cicariu Bridge condition value 2; Damage requires monitoring or maintenance in the future. Cimanuk Bridge, Jalan Bayongbong, bridge condition score 1; Damage can be repaired through routine maintenance.